Basic Muamalah Values As Guidelines For Ethical Digital Business Conduct - hendra; Surya Sukti (LP2M IAIN Palopo, 2026)
The development of the digital economy has significantly expanded the scope of modern business activities while creating complex ethical challenges such as information asymmetry, data misuse, and non-transparent transaction practices. This study aims to analyze the scope of digital business, explain the role of fiqh muamalah as a behavioral guideline, and elaborate on the fundamental muamalah values that serve as ethical guidelines in digital business practices. Using a library research method, this study reviews literature on fiqh muamalah, Islamic economics, and contemporary research related to economic digitalization. The findings indicate that digital business encompasses a wide range of technology-based transactions that require a strong ethical framework; fiqh muamalah functions as a normative guide ensuring justice, honesty, transparency, and consumer protection; and fundamental muamalah values such as trustworthiness (amanah), honesty (ṣidq), justice, avoidance of gharar, and maslahah are highly relevant in building ethical and sustainable digital business practices. The study concludes that integrating muamalah principles is essential to establishing a trustworthy, fair, and responsible digital business ecosystem.